Spatial Equilibrium Evaluation and Diagnosis of Regional Water Resources Based on Comprehensive Gini Coefficient and Subtractive Set Pair Potential - DONG Tao; DONG Guoqiang; HU Yong; FENG Yaolong; ZHANG Jun (Renmin Zhujiang)
In order to support economic and social development and high-quality development of water conservancy, it is crucial to scientifically judge the spatial equilibrium state of regional water resources. Therefore, the Lorentz curve matching water resources with population and GDP was constructed, and the population and GDP were weighted. The comprehensive Gini coefficient of each element after matching regional water resources was calculated to judge the spatial equilibrium state. Subtractive set pair potential was used to identify vulnerable regions affecting the spatial equilibrium of regional water resources. A comprehensive evaluation model of spatial equilibrium of regional water resources based on the Gini coefficient and subtractive set pair potential was established and applied to Chongqing. The findings demonstrate that the water resources in Chongqing are generally in an unbalanced spatial state from 2015 to 2022, particularly in the central city, western regions, and eastern new cities of Chongqing. Concurrently, the subtractive set pair potential in these three regions, manifested as partial reverse potential or reverse potential, designates them as vulnerable regions that impact the spatial equilibrium state of water resources in Chongqing. In the future, it is necessary to take control measures to improve the equilibrium state in these regions. The evaluation model can provide a reference for the high-quality development of regional water conservancy and optimal allocation of water resources.